A Tau Pathogenesis-Based Network Pharmacology Approach for Exploring the Protections of Chuanxiong Rhizoma in Alzheimer’s Disease - Zeng, Peng; Su, Hong-Fei; Ye, Chao-Yuan; Qiu, Shuo-Wen; Shi, Anbing; Wang, Jian-Zhi; Zhou, Xin-Wen; Tian, Qing (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is the most common cause of neurodegenerative dementia and one of the top medical concerns worldwide. Currently, the approved drugs to treat AD are effective only in treating the symptoms, but do not cure or prevent AD. Although the exact causes of AD are not understood, it is recognized that tau aggregation in neurons plays a key role. Chuanxiong Rhizome (CR) has been widely reported effective for brain diseases including dementia. Thus, we explored the protections of CR in AD by a tau pathogenesis based network pharmacology approach. According to the ultra-HPLC with triple quadrupole mass spectrometry data and Lipinski's rule of five, 18 bioactive phytochemicals of CR were screened out. They were shown corresponding to 127 tau pathogenesis related targets, among which EGFA, IL1B, CTNNB1, JUN, ESR1, STAT3, APP, BCL2L1, PTGS2 and PPARG were identified as the core ones. We further analyzed the specific actions of CR active phytochemicals on tau pathogenesis from the aspects of tau aggregation and tau-mediated toxicities. It was shown that neocnidilide, ferulic acid, coniferyl ferulate, levistilide A, Z-ligustilide, butylidenephthalide and caffeic acid be effective in reversing tau hyperphosphorylation. Neocnidilide, senkyunolide A, butylphthalide, butylidenephthalide, Z-ligustilide and L-tryptophan may be effective in promoting lysosome associated degradation of tau. And levistilide A, neocnidilide, ferulic acid, L-tryptophan, senkyunolide A, Z-ligustilide and butylidenephthalide may antagonize tau-mediated impairments of intracellular transport, axon and synaptic damages, and neuron death (especially apoptosis). The present study suggested that acting on tau aggregation and tau-mediated toxicities is part of the therapeutic mechanism of CR against AD.